Does rest breed rust? An examination of DNP-Rest decisions and performance in the National Basketball Association regular and post-season - Pradhan, Sean; Miller, Travis J. (Frontiers in Sports and Active Living, 2022)
Within the National Basketball Association (NBA), players and teams maintain that having healthy players sit out some games during the regular season may help them be more productive during the post-season. This decision to not play in order to rest the player, aptly noted as a DNP-Rest decision on injury reports, is in line with team and player goals, and fits with a growing body of evidence in support of the power of rest for health and performance. However, these practices conflict with some goals of the league, which has a vested interest in having the top talent play to attract broadcasters, advertisers, live spectators, and thus, enhance viewership. The current study is among the first to test the theory that strategically resting healthy players during the regular season results in better performance, as indicated by Player Efficiency Rating (PER) and Win Shares, during the post-season. Utilizing data from the 2016–17 through the 2020–21 NBA seasons, there was not sufficient evidence to suggest that resting more games during the regular season results in better performance in the post-season. Findings from a nested case-control study of 184 players (92 cases; 92 controls) also showed no differences in the change in performance from regular to post-season between cases of players who received rest during the regular season and matched controls. Although the restorative effects of rest might be considerable in the short term, the current study provides additional evidence to suggest that the impact may not carry over into the post-season.